HUBUNGAN KECERDASAN INTERPERSONAL DENGAN KETERAMPILAN MENGELOLA KELAS GURU PAUD SE-KECAMATAN SAIL KOTA PEKANBARU - Winda Elvita Sari; Ria Novianti; Enda Puspitasari (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract: This study background due to determine the relationship between interpersonal intelligence and classroom management skills of early childhood education teachers (PAUD) in Sail sub-district of Pekanbaru city. The population in this study was 32 people of early childhood education teachers (PAUD. The method used in this study was a quantitative correlation to see the relationship between independent variables and dependent variables. The data collection techniques using a questionnaire and Likert scale analysis. The technique of data analysis using a scale test and statistical method analysis by IBM SPSS For Windows Ver. 22. Based on hypothesis test results there is a significant positive relationship between interpersonal intelligence and classroom management skills of early childhood education teachers (PAUD) in Sail sub-district of Pekanbaru city. It can be known from the correlation coefficient of Rxy = 0.394 it is greather than rtable = 2,021(0,394> 2,021) and the level of significance at 0.026 <0.05. Level of relationship between interpersonal intelligence with the classroom management skills of PAUD teachers in whole Sail sub-district of Pekanbaru City at the low category with determinant coefficient value is equal to KP = r2 x 100% = 15.52% and it means that interpersonal intelligence was affecting the classroom management skills at 15.52%.Keyword: Interpersonal Intelligence, Classroom Management Skills